The Eclipsing Phenomenon in Celebrity Endorsement, Emotional Response, Purchase Intention Based on the Stimulus-Organism-Response Theory - Sumaji, Yoseva Maria Pujirahayu; Kaihatu, Thomas Stefanus; Sutanto, Verrell; Toreh, Fabio Ricardo; Immanuel, Dewi Mustikasari; Azizurrohman, Muhammad (Universitas Brawijaya, Indonesia, 2024)
An advertisement must pay attention to the concepts and strategies in advertising because the use of this endorser can be a double-edged knife for the brand. In the vampire effect phenomenon, celebrity endorsers can potentially overshadow the brand so that the audience focuses only on the celebrity, not the brand. Specifically, the phenomenon of a brand that the celebrity endorser overshadows is called high eclipsing an endorsement, and vice versa for the phenomenon of low eclipsing. This research was conducted to develop a framework that discusses the eclipsing phenomenon in celebrity endorsement in the context of stimulus-organism-response (SOR) theory. The participants in this study were undergraduate students in a department at a well-known university in Surabaya. The characteristics of the Participants are domiciled in Surabaya and are between 18-24 years old. Through this study, we can find out how consumers' emotional response is formed when faced with high- and low-eclipsing advertisement stimuli. In addition, this study will also discuss how the differences in purchase intentions are formed from these two different eclipsing endorsement stimuli. The research indicates a significant positive effect between exposure to advertising content featuring both high-eclipsing (HE) and low-eclipsing (LE) celebrity endorsements and emotional response (EM). It implies that leveraging celebrities in advertisements, regardless of their eclipsing status, can evoke a heightened emotional response from the audience. The study suggests a noteworthy association between exposure to advertising content containing celebrity endorsements (CE) and increased purchase intention (PI). Consumers are more likely to desire to purchase a product or service when it is endorsed by a celebrity, indicating the potential effectiveness of this marketing strategy.